Industrial Agglomeration and Economic Development - Kurt A. Hafner (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2004)
The paper outlines a static equilibrium model, which analyses the economic development in a two-country case by considering interregional migration in R&D-sectors. The effects of migration and firm decisions on both industrial agglomeration and economic development will be shown: lock-in-effects and free market entry will lead to a concentration of firms. In addition, the consideration of fundamental and secondary research activity leads to a higher number of firms and products by means of cost reduction and spillover effects. The resulting demand of unskilled and skilled labor will be met by sectoral and interregional migration. This reinforces the concentration of economic activity and leads to a higher degree of specialization and economic development. The formation of single equilibria is shown under consideration of exogenous shocks: diminishing transportation cost will turn economies, originally equally endowed and with the same economic structure, to spatial concentration and uneven economic development.
Keywords: R0; O1; D5; 330; Economic geography; Factor mobility; Regional growth theory; R&D; Learning by doing; Spillover effects; Regionale Konzentration; Neue ökonomische Geographie; Faktormobilität; Forschung; Hochtechnologiesektor; Lernprozess; Spillover-Effekt; Entwicklung; Theorie